Efektivitas Video Edukasi Premenstrual Syndrom terhadap Pengetahuan, Perilaku dan Tingkat Kecemasan pada Remaja Putri - Raswati Teja, Ni Made Ayu Yulia; Dewi, Ni Wayan Erviana Puspita; Indriana, Ni Putu Riza Kurnia; Diyu, Ida Ayu Ningrat Pangruating (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Premenstrual syndrome (PMS) is a symptoms of physical and mental disorders, which usually appear from one week to several days before menstruation comes, and disappear after menstruation comes, although sometimes it lasts until menstruation stops. PMS which occurs in teenagers can reduce productivity in carrying out daily activities. PMS symptoms in teenagers can affect their performance at school. The incidence of PMS affects activities at school, for example: decreased concentration in learning, disruption of communication with friends, it is also possible that there will be a decrease in learning productivity and an increase in absenteeism and attendance. The purpose this research was to determine the effectiveness of premenstrual syndrome educational videos on the knowledge, behavior and stress levels of teenager at Senior high School 1 Dawan Klungkung. This research are pre-experimental design with  one-group pretest-post-test desaign. This research location was at Senior high School 1  DawanKlungkung. Analysis data was used univariate analysis, bivariate analysis with Wilcoxon test. The results of this study show that educational videos are effective in increasing knowledge and behavior as well as reducing the anxiety level of teenager with premenstrual syndrome with a p value of 0.0001. Educational videos are effective to increasing knowledge and behavior as well as reducing the anxiety level of teenager with premenstrual syndrome  Keywords: Educational Video, Knowledge, Behavior and Anxiety Level  ABSTRAK Premenstrual syndrome (PMS) adalah sekumpulan gejala berupa gangguan fisik dan mental, yang biasanya muncul mulai satu minggu sampai beberapa hari sebelum datangnya haid, dan menghilang sesudah haid datang, walaupun kadang berlangsung sampai haid berhenti PMS yang terjadi pada remaja dapat menurunkan produktivitas dalammelakukan aktivitas sehari-hari. Gejala-gejala PMS pada remaja dapat berpengaruh terhadap prestasinya di sekolah. Kejadian PMS mempengaruhi kegiatan di sekolah, misalnya: penurunan konsentrasi belajar, terganggunya komunikasi dengan teman juga dimungkinkan terjadi penurunan produktivitas belajar dan peningkatan absensi kehadiran. Tujuan penelitian ini adalah untuk mengetahui Efektivitas video edukasi premenstrual syndrom dengan pengetahuan, perilaku dan tingkat stress remaja putri di SMAN 1 Dawan Klungkung. Penelitian ini bersifat analitik dengan desain pre eksperimental dengan pendekatan one- group pretest-post-test. Tempat penelitian yaitu di SMA 1 Dawan Klungkung. Analisa data yang digunakan yaitu analisis univariat, analisis bivariat dengan uji Wilcoxon. Hasil penelitian ini menunjukkan bahwa video edukasi efektif terhadap peningkatan pengetahuan dan perilaku serta penurunan tingkat kecemasan remaja putri dalam menghadapi premenstrual syndrome dengan p value 0,0001. Video edukasi efektif dalam peningkatan pengetahuan dan perilaku serta penurunan tingkat kecemasan remaja putri dalam menghadapi premenstrual syndrome Kata Kunci: Video Edukasi, Pengetahuan, Perilaku dan Tingkat Kecemasan